Clinical Evaluation of Two Non-Invasive Genetic Tests for Detection and Monitoring of Urothelial Carcinoma: Validation of UroVysion and Xpert Bladder Cancer Detection Test - Kavcic, Niko; Peric, Ivan; Zagorac, Andreja; Kokalj Vokac, Nadja (Frontiers in Genetics, 2022)
A variety of commercially available urinary molecular markers have been introduced for detecting and monitoring urothelial carcinoma (UC). We prospectively evaluated the UroVysionTM Bladder Cancer Kit (FISH) and the Xpert® Bladder Cancer Detection (Xpert) test. Both tests were performed on voided urine samples after negative cystoscopy and negative abdominal ultrasound (US) and/or negative computed tomography urography (CTU). Urine specimens from 156 patients diagnosed with hematuria and suspected of having UC and 48 patients followed up after treatment of UC were analyzed using FISH and Xpert. Among 204 patients, 20 had UC, 11 located in the bladder, 6 in the ureter, and 3 in the renal pelvis. FISH had an overall sensitivity (SN) of 78%, a specificity (SP) of 93%, and a negative predictive value (NPV) of 96%. Xpert had an overall SN of 90%, an SP of 85%, and an NPV of 98%. Both tests had high SN, SP, and NPV. The SP of FISH was significantly higher. By using FISH and Xpert in addition to cystoscopy, renal and bladder US, and/or CTU in the diagnostic workup of patients with hematuria and follow-up after transurethral resection of the bladder (TURB), a substantial number of patients (10%) otherwise missed was discovered to have UC.